The population of Friuli Venezia Giulia. Future scenarios (2016-2040) - FORNASIN, ALESSIO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2016)
In a recent conference, which took place in Udine in June 2016, the case of the demographic dynamics of Friuli Venezia Giulia in the near future has been brought to the attention of the public. My aim is to foresee some of the features of the population of Friuli Venezia Giulia in the near future and its main problems related to the regional productive system’s demand for manpower. In this paper, I will present a series of scenarios concerning the evolution of the population in Friuli Venezia Giulia from 2016 to 2040. All the scenarios have been built applying the cohort component method